Sustainable Development Goals: Peran Blue Economy dan Digital Accounting Pada Pengembangan UMKM Pesisir Kabupaten Serdang Bedagai - Rahmadani Rahmadani; Nurhaflah Soraya; Muhammad Asrin Jazuli; Khairi Anshor (Worksheet : Jurnal Akuntansi, 2026)
This study provides an overview of the role of the blue economy and digital accounting in the development of coastal MSMEs. Another important aspect is the creation of sustainable development. The purpose of this study is to obtain information related to the development of coastal MSMEs through the blue economy and digital accounting concepts. The long-term objective of this research is to provide coastal MSMEs with literacy on how the blue economy is increasingly relevant in economic, social, and environmental terms in overcoming various challenges in coastal areas that have abundant marine potential and wealth, supported by digital accounting for financial management for MSME development and improving the economic level of local communities and sustainability. This research is qualitative research by analyzing data using NVivo software. Data collection techniques were carried out using interviews, observation, and documentation. This research was conducted at the Dungun Serdang Bedagai Salted Fish MSME. The results of this study are in the form of a Business Model Canvas (BMC) with the concepts of the blue economy and digital accounting in the Dungun Salted Fish MSME. The concepts of the blue economy and digital accounting have complex interrelationships in various aspects that affect the development and sustainability of the Dungun Salted Fish Coastal MSME in Serdang Bedagai Regency.